The Dominant-Subthalamic Nucleus Phenomenon in Bilateral Deep Brain Stimulation for Parkinson’s Disease: Evidence from a Gait Analysis Study - Rizzone, Mario Giorgio; Ferrarin, Maurizio; Lanotte, Michele Maria; Lopiano, Leonardo; Carpinella, Ilaria (Frontiers in Neurology, 2017)
Background It has been suggested that parkinsonian (PD) patients might have a ‘dominant’ (DOM) subthalamic nucleus (STN), whose unilateral electrical stimulation (DBS) could lead to an improvement in PD symptoms similar to bilateral STN-DBS. Objectives Since disability in PD patients is often related to gait problems, in the present study we wanted to investigate in a group of patients bilaterally implanted for STN-DBS: 1) if it was possible to identify a sub-group of subjects with a dominant-STN; 2) in the case, if the unilateral stimulation of the dominant-STN was capable to improve gait abnormalities, as assessed by instrumented multifactorial gait analysis, similarly to what observed with bilateral stimulation. Methods We studied 10 PD patients with bilateral STN-DBS. A clinical evaluation and a kinematic, kinetic and electromyographic analysis of overground walking was performed -off medication- in 4 conditions: without stimulation, with bilateral stimulation, with unilateral right or left STN-DBS. Through a hierarchical agglomerative cluster analysis based on motor UPDRS scores it was possible to separate patients into two groups, based on the presence (6 patients, DOM-group) or absence (4 patients, NDOM-group) of a dominant STN. Results In the DOM-group, both bilateral and unilateral stimulation of the dominant STN significantly increased gait speed, stride length, range of motion of lower limb joints and peaks of moment and power at the ankle joint; moreover, the electromyographic activation pattern of distal leg muscles was improved. The unilateral stimulation of the non-dominant STN did not produce any significant effect. In the NDOM-group only bilateral stimulation determined a significant improvement of gait parameters. Conclusions In the DOM-group the effect of unilateral stimulation of the dominant STN determined an improvement of gait parameters similar to bilateral stimulation. The pre-surgical identification of these patients, if possible, could allow to reduce the surgical risks and side effects of DBS adopting a unilateral approach.